2013
DOI: 10.5296/ijele.v1i3.3492
|View full text |Cite
|
Sign up to set email alerts
|

Writing in the Foreign Language Classroom: The Effects of Prompts on the Iranian Learners of English

Abstract: The present study intended to inspect whether different prompts (bare, vocabulary, and prose model) could exert different effects on the overall quality of the Iranian intermediate EFL learners' writing performances or not, and in case of effect, which of the prompts was efficacious toward the enhancement of the participants' overall writing quality. Forty male and female Iranian intermediate students learning English as a foreign language were selected via administering the Preliminary English Test (PET) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Additionally, the general trend observed was that prompts with more task elements yielded higher average scores at the group level. These results corroborate previous findings that writing prompts with higher cognitive demands may produce higher quality essays than bare prompts (Bahrebar & Darabad, 2013; Way et al, 2000; Robinson, 2001). With respect to the use of the continuation task in high-stakes testing contexts, our results provide empirical support for Liu and Chen’s (2016) recommendation that more specific task prompts, such as those that provide an opening sentence for each paragraph and that require the use of particular key words, can be considered to allow learners to demonstrate their writing ability more fully.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the general trend observed was that prompts with more task elements yielded higher average scores at the group level. These results corroborate previous findings that writing prompts with higher cognitive demands may produce higher quality essays than bare prompts (Bahrebar & Darabad, 2013; Way et al, 2000; Robinson, 2001). With respect to the use of the continuation task in high-stakes testing contexts, our results provide empirical support for Liu and Chen’s (2016) recommendation that more specific task prompts, such as those that provide an opening sentence for each paragraph and that require the use of particular key words, can be considered to allow learners to demonstrate their writing ability more fully.…”
Section: Discussionsupporting
confidence: 91%
“…They found that the prose model prompt produced the highest mean writing scores and the bare prompt the lowest. Bahrebar and Darabad (2013) reported similar results in their examination of the effects of the same three prompt types on the overall writing quality of Iranian intermediate EFL learners. In terms of textual features, it has been reported that a more explicit prompt tended to elicit more fluent and accurate production (Way et al, 2000), lower syntactic complexity (O’Loughlin & Wigglesworth, 2007), and more varied modes of argumentation (He & Sun, 2015).…”
Section: Introductionmentioning
confidence: 52%